Il grande eclettico Renato Simoni nel teatro italiano del primo Novecento - Gjata, Adela (Premio Ricerca «Città di Firenze», 2015)
Renato Simoni was a playwright, theatre critic, librettist for opera seria and opera buffa, screenwriter, speaker, author of magazines, ballets, essays, costume articles, epigrams, anacreontics and rhymed jokes, but also one of the first Italian directors. In the 1930s and 1940s, he was at the head of important installations for the Venice Biennale and the Maggio Musicale Fiorentino. Using unpublished archival documents, this volume reconstructs the portrait of a multifaceted and authoritative man of the theatre, whose artistic experience has often been neglected by historiography, and yet refers to a decisive historical moment of theatre in Italy, marked by the progressive dissolution of the chief-comedian-and-showman structure in theatrical troupes and by the need for aesthetic and productive renewal.